2007
DOI: 10.1145/1269900.1268794
|View full text |Cite
|
Sign up to set email alerts
|

Breadth-first CS 1 for scientists

Abstract: This paper describes an introductory CS course designed to provide future scientists with a one-semester overview of the discipline. The course takes a breadth-first approach that leverages its students' interest and experience in science, mathematics, and engineering. In contrast to many other styles of CS 1, this course does not presume that its students will study more computer science, but it does seek to prepare them should they choose to do so. In addition to describing the curriculum and resources, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Python's use in academia has grown rapidly in recent years [4,10,20,21,26], leading to the development of several introductory textbooks [11,13,14,15,29]. The attraction generally stems from its clean and simple syntax, allowing students to devote greater effort toward learning conceptual issues and developing applications, with less emphasis on extraneous syntactical details.…”
Section: Python In Educationmentioning
confidence: 99%
“…Python's use in academia has grown rapidly in recent years [4,10,20,21,26], leading to the development of several introductory textbooks [11,13,14,15,29]. The attraction generally stems from its clean and simple syntax, allowing students to devote greater effort toward learning conceptual issues and developing applications, with less emphasis on extraneous syntactical details.…”
Section: Python In Educationmentioning
confidence: 99%
“…Therefore, not only is it problematic if an exclusive focus on programming reduces students' interest in CS, but these programming-centered courses may not lead to the learning outcomes that are most important for a broad student population: namely, an understanding and appreciation of the basic and applied science of computer science. Recently, some institutions have begun offering courses that are "contextualized" to different interest areas, such as engineering or multimedia computation [12], or that offer a "breadth-first" approach to computer science rather than a purely programming-centric pedagogy [1,2,10]. However, while intended to be more appealing to non-CS students, these courses are still centered around programming.…”
Section: Introductionmentioning
confidence: 99%
“…Wing [18] argues persuasively that understanding principles of computation and "computational thinking" is important for everyone, not just computer science. We were also partly inspired by "Great Ideas" and breadth-first programming-centered courses [2,6,10].…”
Section: Introductionmentioning
confidence: 99%
“…While it has been suggested that breadth-first courses for nonmajors might also be considered breadth-last [7], we apply the term breadth-last to CS technical electives which expose majors to the integration of the entire CS core.…”
Section: Introductionmentioning
confidence: 99%